2009
DOI: 10.15288/jsad.2009.70.16
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Context and Drinking Problems Among Black, White, and Hispanic Men and Women in the 1984, 1995, and 2005 U.S. National Alcohol Surveys

Abstract: ABSTRACT. Objective: The purpose of this study was to investigate the preferred drinking contexts of different gender and ethnic groups (white, black, and Hispanic men and women), by examining where these groups do most of their drinking and to what extent drinking contexts preferences are associated with certain drinking-related consequences. Method: The study used data from the 1984, 1995, and 2005 U.S. National Alcohol Surveys. Among current drinkers, cluster analyses of volume drunk in six contexts (restau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 23 publications
8
87
0
Order By: Relevance
“…Prior research has shown that college student drinking events are almost evenly distributed between public (i.e., bars, restaurants) and private (i.e., homes) contexts (Clapp et al, 2000). Moreover, prior investigations of drinking locations have found that the context in which drinking occurs often contributes to the amount of alcohol consumed (Clapp et al, 2006) and is related to a variety of negative consequences (Nyaronga et al, 2009;Wells et al, 2005). Several variables have been examined as to why context infl uences alcohol consumption.…”
Section: Drinking Contextsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research has shown that college student drinking events are almost evenly distributed between public (i.e., bars, restaurants) and private (i.e., homes) contexts (Clapp et al, 2000). Moreover, prior investigations of drinking locations have found that the context in which drinking occurs often contributes to the amount of alcohol consumed (Clapp et al, 2006) and is related to a variety of negative consequences (Nyaronga et al, 2009;Wells et al, 2005). Several variables have been examined as to why context infl uences alcohol consumption.…”
Section: Drinking Contextsmentioning
confidence: 99%
“…Several variables have been examined as to why context infl uences alcohol consumption. Factors such as ethnicity (Nyaronga et al, 2009), gender (Herd and Grube, 1993), lack of supervision (Wells et al, 2005), and living arrangement (Gfroerer et al, 1997;Valliant and Scanlan, 1996;Ward and Gryczynski, 2009) are associated with different contexts of heavier drinking in college. A number of contexts have been examined in relation to alcohol consumption and negative consequences, including home, non-fraternity/sorority parties, fraternity/sorority parties, bars, and sporting events.…”
Section: Drinking Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of 5+ drinking days is strongly associated with nonfatal injury (Cherpitel et al, 1995), drinking and driving (Greenfi eld and Rogers, 1999a), arguments and fi ghts (Nyaronga et al, 2009), and criminal behavior (Greenfi eld, 1998), as well as morbidity (Greenfi eld, 2001) and mortality (Rehm et al, 2006). Even chronic harms, such as alcohol dependence , show a dose-response relationship with 5+ drinking days.…”
mentioning
confidence: 99%